Variability of 24-hour pH-metry scores at patients with duodenal peptic ulcer after single dose of rabeprazole - D. I. Abdulganiyeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
Aim of investigation. To estimate antisecretory response to single dose of rabeprazole in patients with peptic ulcer (PUD) of duodenum by 24-hour intragastric pH-metry.Material and methods. Antisecretory response to oral intake of 20 mg of rabeprazole (pariet) was studied in 48 patients with uncomplicated PUD of duodenum by 24-hour intragastric pH-metry. Results. The antisecretory response to the first dose of rabeprazole was revealed in 43 (89,6%) patients. Resistance to the first dose was found in 5 (10,4%) patients. «Variability of antisecretory response phenomenon» was revealed, that is based on individual differences of antisecretory effect in different patient groups.Conclusion. Original study demonstrated high efficacy of rabeprazole in the first day of intake.